2013
DOI: 10.1111/are.12230
|View full text |Cite
|
Sign up to set email alerts
|

Effect of supplemental feed type on water quality, plankton and benthos availability and carp (Cyprinus carpioL.) growth in semi-intensive monoculture ponds

Abstract: A four‐and‐a‐half months study was conducted in nine earthen ponds to evaluate the addition of different supplemental feeds as a management tool for enhancing natural food availability and common carp growth, while maintaining optimal water quality in the semi‐intensive system. Three supplemental feeds were used: commercial extruded and pelleted feed with 25% protein and 7% fat and cereals. The type of supplemental feed did not influence water quality, except hardness, but significantly affected abundance of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 40 publications
1
8
0
1
Order By: Relevance
“…Water quality parameters were monitored and results were published, showing no differences between ponds, except in the level of water hardness, with following values: for cereal feed: 12.8°dH a ; for PF: 14.0°dH b ; for EF: 13.2°dH ab ( P < 0.01; Ćirić et al . ).…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…Water quality parameters were monitored and results were published, showing no differences between ponds, except in the level of water hardness, with following values: for cereal feed: 12.8°dH a ; for PF: 14.0°dH b ; for EF: 13.2°dH ab ( P < 0.01; Ćirić et al . ).…”
Section: Methodsmentioning
confidence: 97%
“…The design of this experiment is already described in previous article (Ćirić, Subakov‐Simić, Dulić, Bjelanović, Čičovački & Marković ). The experiment was conducted in nine earthen fish ponds at the carp farm ‘Kapetanski rit’ in the northeastern part of Serbia from June to October 2009.…”
Section: Methodsmentioning
confidence: 99%
“…Several other studies have also shown that the use of cereals as a supplementary feed in carp ponds can affect zooplankton composition (e.g. Adámek et al., ; Ćirić et al., ). In the present study, however, different artificial diets had no significant influence on natural food availability (i.e.…”
Section: Discussionmentioning
confidence: 96%
“…() and Ćirić et al. (), who showed that different supplementary feeds (cereals or pelleted and extruded diet) had no effect on water quality in fish ponds. On the contrary, water quality can be strongly influenced by fish biomass: higher densities of carp increase turbidity and nutrient concentration, especially P (Chumchal et al., ; Driver et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the experiment carried out by Ćirić et al [27] showed that protein-enriched feed applied to carp ponds had a positive effect on the development of large Cladocera and Copepoda in the zooplankton of the ponds. Vakkilainen et al [28] also studied the infl uence of predatory fi sh and additional feeding on zooplankton.…”
Section: Discussionmentioning
confidence: 98%